Self-Regulated Learning And Cognitive Processes In Flipped Classroom: A Library Investigation - Nike Aulia Andhini; J. Priyanto Widodo (PT. Gudang Pustaka Cendekia, 2024)
This study investigates how cognitive processes in a flipped classroom setting influence self-regulated learning (SRL). Active student participationand self-directed learning are prioritized in this approach. 13 pertinent papers on flipped classrooms, SRL, and related topics were looked into for theliterature review. The results demonstrated the value of SRL in enhancing students' capacity for autonomous learning and academic success.Collaborative and active learning are further encouraged in the flipped classroom setting. The conclusion for education is that in order to enhancestudent learning outcomes, it is critical to include SRL principles into teaching procedures. Offering students individualized support and unambiguousdirection as they get ready for flipped classroom activities are examples of useful recommendations. Through this research, the function of SRL inflipped classrooms is better understood, and ideas for developing instructional strategies based on SRL principles are gained.